ARGON AND CO2 ON THE RACE TRACK IN SILICATE MELTS: A TOOL FOR THE DEVELOPMENT OF A CO2 SPECIATION AND DIFFUSION MODEL - Nowak M.; Schreen D.; Spickenbom K. (My University, 2004)
We have analysed the kinetics of Argon and CO2 diffusion in simplified iron free rhyolitic to hawaiitic melts using the diffusion couple technique. The concentration distance profiles of Ar and CO2 were measured with electron microprobe analysis and Fourier Transform Infrared Spectroscopy, respectively. Error functions were fitted to the symmetrical concentration distance profiles to extract the diffusion coefficients.In the temperature range 1373 to 1773 K the activation energies for Ar diffusion range from 169 ± 20 to 257 ± 62 kJ mol−1. Ar diffusivity increases exponentially with the degree of depolymerisation. In contrast, the mobility of total CO2, that is identical to Ar mobility in rhyolitic melt, keeps constant with changing bulk composition from rhyolite to hawaiite. CO2 speciation at 1623 K and 500 MPa was modeled for the range of compositions studied using the diffusion data of Ar and total CO2 in combination with network former diffusion calculated from viscosity data. Within error this model is in excellent agreement with CO2 speciation data extrapolated from temperatures near the glass transition temperature for dacitic melt composition. This model shows that even in highly depolymerised hawaiitic and tholeiitic melts molecular CO2 is a stable species and contributes 70 to 80% to the total CO2 diffusion, respectively.